双模式机电复合无级传动功率分流特性分析 - 吉雅太; 王伟达; 项昌乐; 韩立金 (Jixie chuandong)
Electro-mechanical variable transmission（EVT）system can enhance the fuel economy by adjusting the engine operating points,and take full advantage of high efficiency of the mechanical transmission.So it is a good solution for applying the hybrid electrical driving to the heavy vehicle.The two-mode EVT which extends the speed variable range by using multi planetary gears can decrease the power requirement of the motors and the dimension of the planetary gear row.The scheme of the EVT is divided based on the speed split and the torque split.Then the description equations of the power split characteristics are proposed which don’t depend on the planetary combining diagram and the parameters. A two-mode EVT which includes two topology structure of power split is calculated and analyzed by these equations.The analysis results indicate that the description equations of the power split can reflect the common features of a special topology structure,and it is significant for the planetary combining diagram and the parameter configuration of the EVT.